Can TikTok Provide Reliable Information about Orthodontics for Patients?. Issue 2 (3rd April 2022) - Arslan, Semiha; Korkmaz, Yasemin Nur; Buyuk, Suleyman Kutalmış
Abstract: The aim of this study was to investigate the quality and reliability of the information about orthodontics on TikTok by analyzing the related videos using DISCERN tool and Global Quality Scale. Five orthodontic-related "hashtags" were searched, and a total of 250 video posts were reviewed. Non-English and inappropriate content/quality posts were excluded from the study. The videos were evaluated by using Quality Criteria for Consumer Health Information (DISCERN) toolkit and Global Quality Scale (GQS). Most of the posts were posted by dental professionals (68 posts; 55%), followed by dental clinics (23 posts; 19%), layperson (18 posts; 15%), and technician/dental laboratories (13 posts; 11%). The mean DISCERN score (section 1 + section 2) for 122 posts was 38.7/75. The mean overall quality of the 122 posts (section 3) in the DISCERN toolkit was 3.15/5. The average GQS score of 122 posts was 3.18 ± 0.93. The DISCERN and GQS scores did not have significant differences among the groups ( p  > 0.05). The DISCERN and GQS results of evaluated TikTok video posts were moderate quality. DISCERN and GQS scores did not differ significantly between the groups. Orthodontists should warn their patients about the reliability of information on social media platforms and should guide them to the right resources.